Low-frequency REB modulation and acceleration of ions in a supercritical mode during plasma injection - Chupikov, P.T.; Medvedev, D.V.; Onishchenko, I.N.; Panasenko, B.D.; Prokopenko, Yu.V.; Pushkarev, S.S.; Faehl, R.J.; Yegorov, A.M. (Вопросы атомной науки и техники, 2004)
Low-frequency modulation of a high-current relativistic electron beam (REB) and acceleration of ions in the first section of a collective ion accelerator was studied experimentally. Low frequency modulation of supercritical high-REB was obtained due to periodic compensation of a virtual cathode charge by plasma ions. An ion flow was produced by an electric field of virtual cathode when plasma assists. Plasma was formed by the four Bostick plasma guns placed at equal distances along the periphery of the drift chamber. The low-frequency modulation with depth 10 % at frequency 46 MHz was obtained. The ion energy was measured using the magnetic analyzer. The ion energy that probably was obtained in the potential well of the virtual cathode exceeded the REB energy. Експериментально досліджена низькочастотна модуляція сильнострумового релятивістського електронного пучка (РЕП) та прискорення іонів в першій секції двохсекційного колективного прискорювача іонів. Низькочастотна модуляція надкритичного сильнострумового РЕП здійснена періодичною компенсацією віртуального катода іонами плазми. Іонний потік сформований електричним полем віртуального катода. Плазма створена чотирма плазмовими пушками бостіковського типу, розміщеними рівномірно по периферії камери дрейфу в області віртуального катода. Модуляція РЕП з глибиною 10% реалізована на частоті 46 МГц. Енергія іонів виміряна за допомогою магнітного аналізатора. Енергія іонів, яка ймовірно отримана в потенційній ямі віртуального катоду, перевищила енергію РЕП. Экспериментально исследована низкочастотная модуляция сильноточного релятивистского электронного пучка (РЭП) и ускорение ионов в первой секции двухсекционного коллективного ускорителя ионов. Низкочастотная модуляция сверхкритического сильноточного РЭП осуществлена периодической компенсацией виртуального катода ионами плазмы. Ионный поток сформирован электрическим полем виртуального катода. Плазма образована четырьмя плазменными пушками бостиковского типа, расположенными равномерно по периферии камеры дрейфа в области виртуального катода. Модуляция РЭП с глубиной 10% осуществлена на частоте 46 МГц. Энергия ионов измерена с помощью магнитного анализатора. Энергия ионов, которая возможно получена в потенциальной яме виртуального катода, превысила энергию РЭП.